Characteristics and manners of corruptive acts described in feuilletons, records and short stories by Branislav Nušić - Jokovic Pantelic, Milica (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
Branislav Nušić – whose descriptions of corruption and corruptive conduct of individuals and authorities of his time are presented and analyzed in this paper – humorously and accurately depicted situations, manners and character of the participants in corruptive acts. His observations reveal causes, reasons and motives of why people become involved in corruptive activities. Greed and gaining a social status, position and reputation at all costs reflect important character traits of the people resorting to corruption. Nušić particularly describes the use of the joint budget by people in power, bribing for positions in the hierarchy of power and of voters during the election process for members of parliament, the role of nepotism in gaining privileges, promotion and advancement in civil service and the profit provided by such status. Different events involving characters inclined towards corruption are described by Nušić through comic, tragic and farcical plots. The paper is aimed to use Nušić’ s insight into his era to show how corruption as a phenomenon is dangerous when it involves individuals and society, and how difficult it is to stop or eradicate corruption to the extent that it cannot threaten social life. Nušić’s descriptions of corruptive situations are still present in similar forms today. Nušić’s message is that Serbia’s political life is inundated in corruption. By their repetition over time, corruptive cases lead to the formation of corruptive patterns accompanying Serbia’s political life to date.
Keywords: corruption, corruptive pattern, bribe, personal benefit, extortion, elections, nepotism, greediness, abuse, illegality